Posterior Capsule Opacification after Cataract Surgery in Children Over Five Years of Age with Square-edge Hydrophobic versus Hydrophilic Acrylic Intraocular Lenses: A Prospective Randomized Study - Koch, Camila Ribeiro (2020)
OBJECTIVE: To compare the effects of hydrophobic and hydrophilic materials in square-edged acrylic intraocular lenses (IOLs) on the development of posterior capsule opacification (PCO) after pediatric cataract surgery. METHODS: Patients were randomly assigned to group 1 (hydrophobic acrylic square-edged IOLs; 13 eyes) or group 2 (hydrophilic acrylic square-edged IOLs; 13 eyes). The study evaluated PCO rates using Evaluation of Posterior Capsule Opacification (EPCO) 2000 software at one, three, six and 12 months postoperatively. Postoperative measurements also included corrected distance visual acuity (CDVA), neodymium:yttrium-aluminum-garnet (Nd:YAG) capsulotomy and postoperative complications other than PCO. RESULTS: Both groups had significant increases in PCO rates after one year. Comparison of the groups showed no significant differences in the EPCO scores at three (group 1, 0.007±0.016 vs group 2, 0.008±0.014; p=0.830), six (group 1, 0.062±0.103 vs group 2, 0.021±0.023; p=0.184), or twelve months postoperatively (group 1, 0.200±0.193 vs group 2, 0.192±0.138; p=0.902). We also found no significant group differences regarding the change (delta, D) in EPCO scores between three and six months (group 1, 0.055±0.09 vs group 2, 0.013±0.02; p=0.113) or between six and twelve months postoperatively (group 1, 0.139±0.14 vs group 2, 0.171±0.14; p=0.567). Twenty-three percent of patients required Nd:YAG capsulotomy at the twelve-month visit. CONCLUSIONS: No differences in PCO rates were found between hydrophobic and hydrophilic acrylic squareedged IOLs in children between five and twelve years of age at one year of follow-up.